Swept blade influence on aerodynamic performance of steam turbine nozzle cascades - Feng, Zi-Ming; Tan, Jingjing; Liu, Xiaolei; Wei, Cui (Springer, 2018)
To improve the aerodynamic performance of steam turbine nozzle cascades, it is significant to study the effect of swept blades to control the flow field within the cascade. Numerical simulations of three different sweep angle blades (−20°, +20° and 0°) were carried out, using CFD modelling. Simulation results showed that the aft-swept blade can effectively improve the corresponding flow characteristics and reduce the total pressure loss. Meanwhile, it has better aerodynamic performance than the straight blade and the fore-swept blade.
Keywords: Aft-swept blade; fore-swept blade; aerodynamic performance; nozzle cascades